Analysis of interest theory and profit-sharing in the Islamic financial system - Merlinda, Lessiany (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2023)
This article examines the comparison between interest theory in conventional financial systems and profit-sharing theory in Islamic financial systems by integrating religious and economic perspectives. The purpose of this study is to gain a more comprehensive understanding of the practical and ethical implications of both financial systems and how they can be applied to support fair and sustainable economic development. The methodology used is a literature review with in-depth content analysis related to the concepts of interest and profit-sharing from various religious perspectives, including Islam, Christianity, and Judaism. The results show that interest theory dominates conventional financial systems with its various applications, while profit-sharing theory in Islamic financial systems offers a fairer and more efficient alternative with profit and loss distribution based on the actual contributions of each party. This study provides significant insights into understanding the fundamental differences between interest and profit-sharing and offers recommendations for creating a more inclusive and sustainable financial system. However, this research has limitations in terms of empirical analysis and variations in the implementation of the profit-sharing system that need to be further explored in future studies.